2016
DOI: 10.1007/s00402-016-2488-7
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic, aseptic, tibial nonunion: how effective is modified Judet’s osteoperiosteal decortication technique and buttress plating?

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Pseudarthrosis of the tibia can be stabilized with the use of external fixators, bone plates, or intramedullary nails [2,[17][18][19][20]. There are no large population studies evaluating treatment outcomes in aseptic pseudarthrosis of the tibia and comparing the Ilizarov method with internal osteosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pseudarthrosis of the tibia can be stabilized with the use of external fixators, bone plates, or intramedullary nails [2,[17][18][19][20]. There are no large population studies evaluating treatment outcomes in aseptic pseudarthrosis of the tibia and comparing the Ilizarov method with internal osteosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Binod et al presented the results of pseudarthrosis treatment via a modified Judet approach in a group of 35 patients. Bone union was achieved in 100% of patients after a mean of 8.24 months [2]. Megas et al reported the results of 50 patients with nonunion of the tibia being treated with intramedullary nails placed with the use of drilling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no clear consensus on the role of reamed exchange nailing for tibial shaft nonunions. While many studies have shown excellent outcomes in patients following reamed exchange nailing for aseptic tibial shaft nonunions, with a reported union rate of 76% to 96% [5], many other studies suggest the use of newer novel techniques such as plating along with osteoperiosteal decortication or more conventional compressive plating with bone grafts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tibial fractures are the most common long-bone fracture (36.7% of all long-bone fractures in adults) and also happen to be the most common site of long-bone nonunion 1 . Patients with nonunion are more likely to have additional fractures during follow-up, to require various types of in-patient and surgical care (including amputation), to be prescribed pain medications (especially strong opioids), and to use more outpatient physical therapy than those with proper bony union 2 .…”
Section: Introductionmentioning
confidence: 99%